2020
DOI: 10.1038/s41586-020-2117-z
|View full text |Cite
|
Sign up to set email alerts
|

An open-source drug discovery platform enables ultra-large virtual screens

Abstract: On average, an approved drug today costs $2–3 billion and takes over ten years to develop 1 . In part, this is due to expensive and time-consuming wet-lab experiments, poor initial hit compounds, and the high attrition rates in the (pre-)clinical phases. Structure-based virtual screening (SBVS) has the potential to mitigate these problems. With SBVS, the quality of the hits improves with the number of compounds screened 2 . However, despite the fact that la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
448
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 450 publications
(478 citation statements)
references
References 36 publications
(47 reference statements)
2
448
1
Order By: Relevance
“…However, the actual hit rate of a virtual screening using traditional computational methods (10,11) has been rather low, with the vast majority of computationally predicted drug candidates being false positives, because it is difficult to reliably predict protein−ligand binding free energies. Most recently, Gorgulla et al (12) reported an interesting new virtual screening platform, called VirtualFlow, used to screen numerous compounds in order to identify inhibitors of Kelch-like ECH-associated protein 1 (KEAP1), but the hit rate was still not very high. Within 590 compounds predicted by the virtual screening, 69 were found to be KEAP1 binders (with a hit rate of ∼11.7% for detectable binding affinity), and 10 of these compounds were confirmed to be displacers of nuclear factor erythroid-derived 2-related factor 2 (NRF2) with IC 50 < 60 μM (with a hit rate of ∼1.4% under the threshold of IC 50 < 60 μM) (12).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…However, the actual hit rate of a virtual screening using traditional computational methods (10,11) has been rather low, with the vast majority of computationally predicted drug candidates being false positives, because it is difficult to reliably predict protein−ligand binding free energies. Most recently, Gorgulla et al (12) reported an interesting new virtual screening platform, called VirtualFlow, used to screen numerous compounds in order to identify inhibitors of Kelch-like ECH-associated protein 1 (KEAP1), but the hit rate was still not very high. Within 590 compounds predicted by the virtual screening, 69 were found to be KEAP1 binders (with a hit rate of ∼11.7% for detectable binding affinity), and 10 of these compounds were confirmed to be displacers of nuclear factor erythroid-derived 2-related factor 2 (NRF2) with IC 50 < 60 μM (with a hit rate of ∼1.4% under the threshold of IC 50 < 60 μM) (12).…”
Section: Significancementioning
confidence: 99%
“…Most recently, Gorgulla et al (12) reported an interesting new virtual screening platform, called VirtualFlow, used to screen numerous compounds in order to identify inhibitors of Kelch-like ECH-associated protein 1 (KEAP1), but the hit rate was still not very high. Within 590 compounds predicted by the virtual screening, 69 were found to be KEAP1 binders (with a hit rate of ∼11.7% for detectable binding affinity), and 10 of these compounds were confirmed to be displacers of nuclear factor erythroid-derived 2-related factor 2 (NRF2) with IC 50 < 60 μM (with a hit rate of ∼1.4% under the threshold of IC 50 < 60 μM) (12). Obviously, the hit rate of a virtual screening is dependent on the reliability and accuracy of the receptor−ligand binding free energy predictions used in the virtual screening process.…”
Section: Significancementioning
confidence: 99%
“…In our opinion, the huge size of both DNA-encoded libraries and multibillion chemical spaces like the one described herein can be considered as compensation for the increased molecular complexity (provided that efficient in vitro or in silico screening technologies are available to mine these ultra-large libraries). The success stories available in the literature for both technologies ( Goodnow et al., 2017 ; Kunig et al., 2018 ; Lyu et al., 2019 ; Gorgulla et al., 2020 ) can serve as a justification for the above hypothesis.…”
Section: Resultsmentioning
confidence: 97%
“…85% synthesis success rate (i.e., a fraction of experiments that could produce the target compound among all the experiments performed) ( Enamine REAL compounds, 2020 ). Recently, its utility in combination with virtual screening was confirmed by discovery of highly potent AmpC β-lactamase (AmpC) inhibitors, D 4 dopamine receptor ligands ( Lyu et al., 2019 ), and Kelch-like ECH-associated protein 1 (KEAP1) inhibitors ( Gorgulla et al., 2020 ).
Figure 1 A General Principle of the REAL Database Generation Using One-Step Two-Component Reactions
…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there is a growing trend towards ultra-high throughput pipelines for computational drug discovery. Examples include the identification of novel β-lactamase inhibitors and dopamine receptor agonists [23], melatonin receptor ligands [24], or protein-protein interaction inhibitors [25]. Even though these results are exiting and promising, they come with a major restriction.…”
Section: Computational Drug Discoverymentioning
confidence: 99%